Herbal Drugs Applied to Enduring Skin Disorders - Chaudhari, Tanmay (Asian Journal of Pharmaceutics (AJP), 2025)
Skin diseases are a major issue that is faced all over the world. Based on the current analysis, it can be deemed that the highest prevalence rate of an ailment across every age bracket of populace is skin infection. Herbal treatment has been used to cure skin condition for thousands of years. Skin diseases are curable and can be controlled using the under-listed herbal plants. The recurring skin diseases are antitumor, vitiligo, scabies, psoriasis, acne and eczema. Herbal drugs for the treatment of diseases of the skin are famous among the population of many countries. More than half of plant species are utilized in skin ailments treatment. The qualitative research on herbs preparation gave the information to conclude that some of the herbs are beneficial for treating the chronic skin disorders with relatively less side effects so far as the use is concerned and its effectiveness in solving the problems. It is believed that the natural therapy is safe with no harm being experienced. Contained in this summary are the functions and uses of therapeutic herbs in long-term illnesses of the skin.